The Protective Effect of Resveratrol on Cisplatin Induced Damage in Rat Liver - Ozlem Kara; Asuman Kilitci (Haseki Tıp Bülteni, 2022)

(untitled)
Aim:One of the underlying causes of cisplatin-induced hepatotoxicity is oxidative stress. We assessed the effect of an antioxidant, resveratrol, on cisplatin-induced damage in the rat liver.Methods:The project-starting date was designed as 01.10.2020 and the project-ending date was planned as 01.04.2021. Three groups were created with 30 female Wistar-Albino rats: In group 1 (control group), 1 mL of 0.9% NaCl (saline) was administered intraperitoneally for 3 days. In group 2 (cisplatin group), 7.5 mg/kg intraperitoneal cisplatin was given for 3 days. In group 3 (cisplatin + resveratrol group), 7.5 mg/kg cisplatin and 10 mg/kg resveratrol were given via the intraperitoneal route. The livers were surgically extirpated in all the groups. In both blood and tissues, malondialdehyde (MDA) levels and activities of catalase (CAT) and superoxide dismutase (SOD) were measured. Also, toxicity markers such as hepatocyte damage (cellular changes), inflammation, hemorrhage, congestion, fibrosis, disorganization of the hepatic cords, and necrosis were assessed by examining the preparations prepared from hepatic tissue with light microscopy and immunohistochemistry.Results:Histopathological tissue damage was significantly higher in group 2 than in other groups (p 0.03). MDA levels were significantly higher and the activities of SOD and CAT were lower in group 2 than in the other groups (p=0.04 and p=0.01, respectively).Conclusion:According to our short-term findings, resveratrol might be an effective molecule for preventing the harmful effects of cisplatin in the rat liver.